Automatic Deodorization and Toilet Cleaning System - DANIEL, HAFIZUL; ROSLAN, Ts HAZLI; SARI, SUHAILA (Progress in Engineering Application and Technology, 2023)
Living in today's time, the bustle of work makes the human commitment to clean up their homes and living areas, especially the toilet area, diminished. To address this issue, an automatic toilet deodorization and cleaning system was developed to ensure that the toilet environment is clean and can work automatically. The developed system consists of several parts such as a watering part for draining water and soap to the floor part of the toilet, a ventilated part to keep the room in the toilet always good, a lighting part to ensure sufficient lighting in the toilet, an input sensor part as a determinant of the presence of the use of the toilet or toilet in use, the display part of the process as an indicator of the toilet user,   The control part is Microcontroller (Arduino) to control the entire system and power supply parts to enable the entire system to get enough power supply. When the input sensor receives a user presence signal, the LCD display and LED indicator will provide information and temperature readings related to the toilet. The system will be activated and equipment such as lights and fans will be turned on. Once the user has finished using the toilet, the system will perform the process of watering water and soap into the toilet to ensure that the floor is clean. The LCD display and LED indicator will again display toilet information for the next user. The next toilet user will feel more comfortable with the information provided through the display and indicators and clean toilet floor conditions before entering the toilet.